Macapat Aesthetic Education in Contemporary Era: the Descriptive Analysis of Tembang Pangkur and Maskumambang on Wayang Kekayon Khalifah - Lutfianto Lutfianto; Suwarna Dwijonagoro (Perhimpunan Intelektual Muslim Indonesia, 2022)
Macapat is a traditional New Javanese poem in the form of a tembang bound by established conventions. The conventions are guru gatra 'number of lines per verse', guru wilangan 'number of syllables in an array', and guru lagu 'sound of syllables at the end of the line'. Singing poetry is because in its reading it is sung. Tembang macapat is based on the beauty of the titillaras arrangement of 'notations' that match the meter pattern. The art of the beauty of this macapat song has been used since around the XV century AD until now. The use of this macapat song is used in various writings, one of which in the contemporary era is in the Wayang Kekayon Khalifah. The author wants to present the beauty of the macapat song in Wayang Kekayon Khalifah as an effort to present education through songs in the present or contemporary era. There are two macapat songs that the writer presents, namely, Maskumambang and Pangkur. It aims to help the reader understand the song's beauty when used for educational facilities. The results of this paper indicate that the macapat songs of Maskumambang and Pangkur can present beauty in the present era of education. The macapat song in the Wayang Kekayon Khalifah gives the old color of new packaging in the world of education. So that macapat can still be present with its beauty in the present era.